Yield components of triploid and tetraploid Musa genotypes in Nigeria - Baiyeri, K.; Mbah, B.; Tenkouano, A. (2000)
The additive main effects and multiplicative interaction (AMMI) model was used to evaluate the stability patterns of 36 Musa genotypes in four cropping environments for bunch weight, pulp weight, and dry matter content. Alleycropping generally induced higher means for all traits than did sole cropping. The triploid plantains produced smaller bunch weights and were less stable than dessert and cooking bananas. In this ploidy group, bunch weight was highest for the cooking bananas `Cardaba' and `Fougamou', but only `Fougamou' was stable across environments. Among the hybrids, only `FHIA23' (dessert banana) expressed high and stable bunch weights, while other high-yielding hybrids displayed specific adaptation to alleycropping. Pulp weight was lower but more stable in plantains than in other triploid genotypes. Among the hybrids, pulp weight was high and stable for one cooking banana (`FHIA3'), one dessert banana (`FHIA1'), and three plantains (`PITA1', `PITA2', and `PITA7'). Dry matter content was highest in plantains and lowest in dessert bananas at both triploid and tetraploid levels, and was also more stable than the other traits. Thus, the adaptation patterns of genotypes across environments varied according to the trait studied. When rank changes were not observed across traits for a given genotype, differences were still noted in the relative magnitude of the IPCA1 score. Hence, both farm gate traits and postharvest processing traits should be considered in selecting for broad or specific adaptation. Determination of the genetic relationships between processing traits and farm gate traits could allow Musa breeders to construct selection indices that would facilitate multiple trait selection and enhance breeding efficiency, with respect to cultivar stability and adaptation across environments.